A web analytics approach to map the influence and reach of CCAFS - Carneiro, Bia; Resce, Giuliano; Ma, Yixin; Pacillo, Grazia; Läderach, Peter R.D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This evaluation sought to understand CCAFS’ influence in motivating actors to tackle climate change. In CCAFS’ theory of change, a cross-cutting aim is to work with strategic partners to “foster policy and institutional change” that will enable large-scale CSA adoption. A conceptual framework was developed, and an innovative approach based on the Digital Methods epistemology was employed to explore the dynamics of knowledge dissemination and changes in attitude towards CSA among stakeholders at various levels. It considered online networks and narratives as evidence of “offline” program influence. Results show that CCAFS has inspired positive change in government policy; built a global community for climate adaption; and sparked public interest in “Climate Smart Agriculture”.